From The Lyrics To Digital Platforms: a Lyrical Autoethnographic Study of The Album Senandung Mubarock as Practice Educational Sociotechnology - Wildan Fauzi Mubarock; Suminto A. Sayuti; Wiyatmi Wiyatmi (Jurnal Mamangan, 2025)
Development digital technology has change method arts and education interact in society. Music and poetry now No only functioning as expression aesthetic, but also as a medium for literacy and learning based technology. Research This aim analyze Senandung album transformation Mubarock from expression lyrics towards digital platforms as well the implications as practice sociotechnology education. Research methods use approach qualitative with autoethnography lyrical, supported digital documentation and response audience. Data obtained from lyrics songs, notes reflective writers, digital publications via YouTube, Spotify, literacy barcodes, as well as comment online audience. Analysis done through interpretation lyrical and reading sociotechnology with framework sociotechnical systems. Research results show that album distribution through digital platforms expands range audience, strengthening digital literacy, and present learning affective -spiritual in context education. Findings This confirm that mediated art technology can functioning as instrument innovation social and education in the Society 5.0 era